Hydrodynamic Evaluation of the Cretaceous Aquifer in the Northwestern Part of the Coastal Sedimentary Basin of Benin (West Africa) - ADISSIN GLODJI, COSSI LUC (My University, 2019)
The main theme of this study is the knowledge of areas favorable to the mobilization of water resources in the Mono catchment area. The use of numerous methods of underground hydrodynamics combined with mapping has allowed us to have an understanding of the areas of high hydrogeological potentiality of the Upper Cretaceous aquifer in this Mono River basin. The evaluation of the hydrodynamic parameters from the Cooper-Jacob line has shown that the transmissivity values at the north of the Cretaceous aquifer of the Mono river catchment are of the order 10-4 to 10-5 m² / s. These transmissivities are of middle class and show that Cretaceous is sterile at the north of the coastal sedimentary basin. In the center of the aquifer, the transmissivity values obtained are of the order of 10-3 m² / s with the exception of the drilling of the locality Bébéhoué. These transmissivities are of strong class and prove the good productivity of the Upper Cretaceous aquifer. Piezometry of the study area has shown that the direction of the underground flows of the Cretaceous aquifer is North-South in the Mono River watershed.
Keywords: transmissivity; Mono River; Piezometry; Upper Cretaceous; aquifer; Benin